Analisis Persepsi Konsumen terhadap Kualitas Produk Keramik Merek Milan di Surabaya - Susanti, C. Esti (Jurnal Widya Manajemen & Akuntansi, 2003)
The purpose of this study is to investigates perception of consumer in Surabaya on product quality variables of Milan Ceramics and what variable of product quality that has the best perception of consumer. The primary data were gathered from 30 respondents. There research data were analyzed using Mean and deviation standard. The result of this study shows that: 1) Perception of consumer in Surabaya on product quality variables of Milan Ceramics is good and 2) Variable of product quality that has the best perception of consumer in Surabaya is Augmented product.